Asymptomatic Bacteriuria in Pregnancy Causes and Incidence - Ali, Sadia; Ghani, Nafeesa; Ali, Ziad; Ali, Yamna (Journal of Gandhara Medical and Dental Science, 2024)
OBJECTIVES This study aims to provide an understanding of asymptomatic bacteriuria in pregnancy by examining its frequency, causative agent, and potential strategies for detection and management. METHODOLOGY A cross-sectional study was conducted in the Department of Obstetrics and Gynecology, PGMI Hayatabad Medical Complex, Peshawar, from July to December 2022. The study included 117 antenatal patients with varying gestational periods attending the OPD. Patients with a history of antibiotic therapy, urinary frequency and dysuria, vaginal discharge, renal tract anomalies, and medical disorders were excluded. Demographic details were recorded, and urine samples were collected and cultured. Data was analyzed using SPSS version 22. RESULTS The incidence of asymptomatic bacteriuria was 25.5%, among 117 women, with E. coli (53.3%) the most common pathogen responsible for the infection, followed by Klebsiella (36.7%) and staphylococcus (10%). CONCLUSION Bacteriuria without causing any symptoms is quite common in pregnancy. Simple measures like screening early in pregnancy can timely detect positive cases and with targeted treatment, both maternal and neonatal morbidity can be curtailed.